POLITIK RUANG GENDER PADA PERMUKIMAN TANEYAN LANJHANG SUMENEP - Wismantara, Pudji Pratitis (EGALITA, 2009)
For centuries, the discourse of knowledge has been built on the experience, expression of thought, and perception of men about the world. While life experience, ideas, thoughts, and the need of space for women are relatively marginalized. This paper was about to reveal ‘symbolic violence’ in the un- derstanding and interpretation of settlement space in the public taneyan lanjhang Sumenep Madura. This violence is male initiated by dictating how to think, act, even how to construct a space for women. With the unfolding of ‘symbolic violence’ in the settlement of this taneyan lanjhang, we must be careful in designing architectural space and try to focus on the design- conscious gender.Keyword: Politik Ruang, Taneyan lanjhang, ’Kekerasan Simbolis’